2006
DOI: 10.1080/00016350600801709
|View full text |Cite
|
Sign up to set email alerts
|

Salivary mutans streptococci and lactobacilli levels after ingestion of the probiotic bacteriumLactobacillus reuteriATCC 55730 by straws or tablets

Abstract: A short-term daily ingestion of lactobacilli-derived probiotics delivered by prepared straws or lozenges reduced the levels of salivary mutans streptococci in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
179
3
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(193 citation statements)
references
References 18 publications
5
179
3
6
Order By: Relevance
“…Several studies suggested that probiotics might also be of benefit for oral health (Meurmann, 2005;Ç aglar et al, 2006;Meurmann and Stamatova, 2007). Several clinical studies demonstrated that a regular consumption of probiotic lactobacilli and Bifidobacterium decreased the number of cariogenic streptococci in saliva and dental plaque, resulting in a significant lower risk of caries (Näse et al, 2001;Ahola et al, 2002;Ç aglar et al, 2006;Ç aglar et al, 2007;Cildir et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that probiotics might also be of benefit for oral health (Meurmann, 2005;Ç aglar et al, 2006;Meurmann and Stamatova, 2007). Several clinical studies demonstrated that a regular consumption of probiotic lactobacilli and Bifidobacterium decreased the number of cariogenic streptococci in saliva and dental plaque, resulting in a significant lower risk of caries (Näse et al, 2001;Ahola et al, 2002;Ç aglar et al, 2006;Ç aglar et al, 2007;Cildir et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that direct contact with oral tissues is not a prerequisite for probiotics to have a beneficial effect; purely systemic administration of a probiotic could enhance lactobacillus proliferation in the oral cavity. 8,9,22 The conflicting results for probiotic efficacy among previous studies are probably attributable to differences among strains of the same species. 24 At present, most research is carried out with well-defined dairy-based live lactobacillus strains.…”
Section: Discussionmentioning
confidence: 40%
“…8,21,22,23 The post-treatment reductions were not directly dependent on the delivery vehicles, which included milk, cheese, yogurt, lozenges, and straws prepared with freeze-dried strains. Çaglar et al 8 investigated whether slowly melting tablets facilitate a more thorough contact between the probiotic and the oral environment compared with a direct swallowing pattern from a straw. Both methods of administration equally reduced the prevalence of salivary mutans streptococci after 2 weeks of use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations